Effects of shear reinforcement on modolus of rupture in concrete beam - Saleh Al Waeel, Osamah Najib (2018)
The flexural strength is one of the mechanical properties of concrete. The flexural strength of concrete is needed to determine the maximum deflection and also maximum loads that concrete can maintain at certain times. Shear reinforcements, which are nor-mally provided as vertical stirrups, are placed at varying intervals depending upon the shear conditions acting on a beam. The flexural failure in reinforced concrete beams does not happen suddenly but instead it shows some warning of distress that will occur in the near future. Contradictory to this, the shear failure is sudden, catastrophic and devastat-ing. To avoid any such sudden shear failure, shear reinforcements are provided. Also, the shear reinforcement has a control over the shear strength of the beam. The shear stirrups and are used to increase the shear strength of concrete beams, to avoid the shear failure and to cause a flexural failure. The main aim of this research is to study the effects of shear reinforcement on flexural strength in concrete beam. The concrete mixture used in the present study consists of cement, course aggregates, fine aggregates and water. Two types of tests i.e. compressive and flexural were carried out. The samples for compressive strength included cubes with size of 150 mm x 150 mm x 150 mm, while the size of the beams used for flexural strength tests were 150 mm width x 150mm depth x 750mm length. The results show there is no difference in flexural capacity between 3 shear links and 4 shear links, but when add 5 shear links we notice slight increase in the flexural capacity, it is concluded that the addition of links as shear reinforcement slightly effect the flexural capacity.